Differentiation of axon-related Schwann cells in vitro. I. Ascorbic acid regulates basal lamina assembly and myelin formation (The Rockefeller University Press, 1987)
Rat Schwann cells cultured with dorsal root ganglion neurons in a serum- free defined medium fail to ensheathe or myelinate axons or assemble basal laminae. Replacement of defined medium with medium that contains human placental serum (HPS) and chick embryo extract (EE) results in both basal lamina and myelin formation. In the present study, the individual effects of HPS and EE on basal lamina assembly and on myelin formation by Schwann cells cultured with neurons have been examined. Some batches of HPS were unable to promote myelin formation in the absence of EE, as assessed by quantitative evaluation of cultures stained with Sudan black; such HPS also failed to promote basal lamina assembly, as assessed by immunofluorescence using antibodies against laminin, type IV collagen, and heparan sulfate proteoglycan. The addition of EE or L-ascorbic acid with such HPS led to the formation of large quantities of myelin and to the assembly of basal laminae. Pretreatment of EE with ascorbic acid oxidase abolished the EE activity, whereas trypsin did not. Other batches of HPS were found to promote both basal lamina and myelin formation in the absence of either EE or ascorbic acid. Ascorbic acid oxidase treatment or dialysis of these batches of HPS abolished their ability to promote Schwann cell differentiation, whereas the subsequent addition of ascorbic acid restored that ability. Ascorbic acid in the absence of serum was relatively ineffective in promoting either basal lamina or myelin formation. Fetal bovine serum was as effective as HPS in allowing ascorbic acid (and several analogs but not other reducing agents) to manifest its ability to promote Schwann cell differentiation. We suggest that ascorbic acid promotes Schwann cell myelin formation by enabling the Schwann cell to assemble a basal lamina, which is required for complete differentiation.